Characterization of Antimicrobial-Producing Beneficial Bacteria Isolated from Huanglongbing Escape Citrus Trees - Riera, Nadia; Handique, Utpal; Zhang, Yunzeng; Dewdney, Megan M.; Wang, Nian (Frontiers in Microbiology, 2017)
The microbiome associated with crop plants has a strong impact on their health and productivity. Candidatus Liberibacter asiaticus (Las), the bacterial pathogen responsible for Huanglongbing (HLB) disease, lives inside the phloem of citrus plants including the root system. It has been suggested that Las negatively affects citrus microbiome. On the other hand, members of citrus microbiome also influence the interaction between Las and citrus. Here, we report the isolation and characterization of multiple putative beneficial bacteria from healthy citrus rhizosphere. Firstly, six bacterial strains showing antibacterial activity against two bacteria closely related to Las: Agrobacterium tumefaciens and Sinorhizobium meliloti were selected. Secondly, antimicrobial activity against five citrus pathogens from Oomycota and Ascomycota phylum was evaluated. Four bacterial strains belonging to the Stenotrophomonas, Bacilli and Burkholderieae families were shown to have antagonistic activity against the citrus root pathogen Phythopthora nicitianae. The four selected bacteria were sequenced and analyzed to explore genes associated with beneficial traits. Putative antimicrobial biosynthesis gene clusters were predicated. The genomic basis underneath the beneficial traits is discussed.